European Small Business Finance Outlook: May/2012 - Helmut Kraemer-Eis; Frank Lang; Athanasios Kyriakopoulos (European Investment Fund (EIF), 2012)
This European Small Business Finance Outlook (ESBFO) provides an overview of the main markets relevant to EIF (equity1, securitisation, microfinance). It is an update of the ESBFO 2/2011 that was published in December last year. We start by discussing the general market environment, then look at the main aspects of equity finance and the SME Securitisation (SMESec) market. Finally, we briefly highlight important aspects of microfinance in Europe.
Keywords: 330